STRATEGI PENGEMBANGAN PRODUK PEMBIAYAAN MUSYARAKAH PT. BANK ACEH KEPADA PELAKU USAHA UMKM KOTA BANDA ACEH DI MASA PANDEMI - nafisah, nada; Ashal, Farid Fathony; Aulia, Riza (Journal of Sharia Economics, 2022)
This study aims to determine the contribution of gampong funds in the development of BUMG Amarabu, Simeulue Cut District, Simeulue Regency and the role of BUMG in the economic development of the community in Amarabu. This study uses a qualitative approach with a descriptive type of research. Informants consisted of geuchik, village officials, community leaders, BUMG administrators and the community. Data collection techniques are interviews, observation, documentation and literature study. Based on the results of the study, it is known that the contribution of gampong funds in the development of BUMG, Simeulue Cut District, Simeulue Regency includes increasing the income of the BUMG itself through community economic efforts so that Gampong-Owned Enterprises are always active in carrying out their activities in Gampong Amarabu. The role of Gampong-Owned Enterprises in the economic development of the community in Amarabu, Simeulue Cut District, Simeulue Regency includes supporting the strengthening of community business activities in collaborating with various parties who have potential in the field of improving the Amarabu community's business. Accommodating and fostering the community in business activities so that it becomes a source of income that is able to foster motivation and innovation in the business world. Increase community economic resilience through business activities that can create jobs. Keywords: Development Strategy, Musyarakah Financing Products, Bank Aceh, MSME